Development of Integrated Interactive E-Modules for Problem Based Learning in Mathematics Learning for Grade XI Phase F of Senior High School - Yudiana Yudiana; Zelhendri Zen; Abna Hidayati; Mutiara Felicita Amsal; Rayendra (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The transformation of learning under the Independent Curriculum requires digital teaching materials that support active learning and strengthen mathematical problem-solving skills. However, matrix instruction remains dominated by conventional materials, making abstract concepts difficult for students to understand. This study aims to develop a valid, practical, and effective interactive e-module integrated with Problem-Based Learning (PBL) for Grade XI Phase F students. The study employed a Research and Development approach using the 4-D model, comprising define, design, develop, and disseminate stages. Data were collected through validation sheets, practicality questionnaires, and learning outcome tests. The results showed that the e-module achieved 92.68% validity, categorised as very valid, and 98.75% practicality, categorised as very practical. Its effectiveness was demonstrated by an increase in the average score from 31.67 to 92.92, with an N-Gain value of 0.90 in the high category. These findings indicate that the PBL-integrated e-module effectively improves students’ understanding of matrix concepts and mathematical problem-solving skills while supporting the Independent Curriculum.